STRATEGI PEMASARAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) MELALUI INSTAGRAM DI ERA PEMASARAN 4.0 - Ni Komang Mela Tri Utari (Nusantara Hasana Journal, 2022)
The purpose of this study is to understand and describe how MSME marketing strategies through Instagram in the Era of Marketing 4.0. The data collection technique used is an in-depth interview with the owner of Zeen Shake and its customers as many as 70 people. The selection of informants is carried out by purposive sampling method and the data collected is analyzed using Nvivo software version 12. The results of this study showed that Zeen Shake conducted a marketing strategy on Instagram by uploading photos and providing information in captions, providing promos on certain days and also uploading testimonials from consumers. In addition, researchers got new findings, namely Zeen Shake also marketed its products through mouth to mouth marketing or Word of Mouth Marketing (WOMM). In the current era of Marketing 4.0, a new customer path was found, from 4A (Aware, Attitude, Ask, Act Again) to 5A (Aware, Appeal, Ask, Act, Advocate). This happens because of the use of technology that causes everyone to connect with each other. Keywords: Marketing Strategy, Instagram, Word of Mouth Marketing, New Customer Line